Closing the clinical gap: an audit of clinical compliance for early-onset neonatal sepsis management - Sanika Dalvi; Zuzanna Gawlowski (Clinical Medicine, 2025)
Introduction: Early-onset neonatal sepsis (EONS) has been recognised as the third most leading cause of neonatal mortality globally, requiring prompt recognition and intervention.1 The 2022 incidence of EONS in the UK was reported to be 0.7 per 1,000 live births.2 The National Institute for Health and Care Excellence (NICE) quality standards, QS75, provide a framework for neonatal sepsis management.3 This audit retrospectively evaluated adherence to these standards in a secondary care neonatal unit. Methods: A retrospective audit of 56 neonatal cases of suspected or confirmed EONS over 2 months in 2024 were assessed for compliance with NICE QS75. Data collection focused on intrapartum antibiotics prophylaxis (IAP) administration, neonatal risk assessment, timing of first antibiotic dose, adherence to 36-h antibiotic review and communication with parents. Results and Discussion: The audit results revealed variability in adherence to NICE QS75 (Figs 1 and 2).Of the 605 babies born in April and May, 56 neonates were treated because of clinical risk indicators for EONS; only those given empirical antibiotics were included in this analysis. The incidence rate of confirmed or suspected neonatal sepsis was 9.2% of babies born. Mothers received IAP for maternal risk factors, unless none were present during labour. IAP was administered to 18 mothers because of maternal risk factors, but an additional four should have received IAP but delivered too quickly, making the compliance rate 81.81% (18/22). Interventions for EONS were timely, with 89.29% (50/56) receiving antibiotics in less than 1 h, although some delays did occur because of ward acuity, prescription and documentation errors. The 36-h decision was documented for 82.14% (46/56) of neonates, but 10 neonates lacked documentation because of patient transfer, documentation errors and local Trust policy for clinical exceptions. Verbal information was provided to 92.86% (52/56) of parents, but written information was not provided to any.Hospitals globally rely on the Kaiser Permanente Neonatal Early-Onset Sepsis Calculator, but this neonatal unit follows the NICE guideline on maternal risk factors and clinical indicators for antibiotic treatment.4 All neonates with suspected EONS cases were treated promptly based on clinical suspicion, blood cultures and CRP, with empirical antibiotics preventing adverse outcomes. However, potential concerns about antibiotic resistance highlight the need to identify the incidence of resistance in EONS management in the UK.Improving communication to parents was highlighted; written information on EONS and late-onset group B Streptococcus infection is vital to improve health literacy on recognising neonatal infections signs, alleviate parental anxiety and provide support to parents.3 Therefore, to improve compliance, a cost-effective approach is to implement a QR code to Trust-approved patient information leaflets. Conclusions: Although overall compliance with NICE QS75 was satisfactory, a marked improvement in communication with parents is needed. Implementing a QR code will be a simplified cost-effective way that doctors can provide parents with information about EONS.